Gen Z voter behavior in the 2024 presidential election: A virtual ethnographic study on the Instagram accounts of presidential candidates - Fitri, Alifa Nur; Fitri, Fitri; Fabriar, Silvia Riskha; Rachmawati, Farida; Hilmi, Mustofa (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2023)
The 2024 presidential and vice-presidential general election is a topic that is being highlighted by the public, including young voters or what could be called Gen Z. The use of Instagram media by three presidential candidates to launch self-introductions and election campaigns is a reference for Gen Z voters in providing comments and assessment. This research aims to determine the behavior of Gen Z voters in the 2024 presidential election using qualitative ethnographic methods and descriptive analysis. The findings of this study show that Gen Z's behavior in responding to the 2024 presidential election includes two behaviors, namely rational and irrational. The rational behavior of Gen Z is shown by assessing the vision and mission of the presidential candidate pair and their track record of achievements. In contrast, the irrational behavior of Gen Z voters is shown by assessing the presidential candidate pair based on exciting content or popularity, even though it lacks substance. Therefore, these findings contribute to the development of user-based discourse that can deconstruct the dominance of discourse by those in power. This aligns with Islamic communication values in the form of 'freedom of action,' which guarantees each individual to accept or reject a discourse.***Pemilihan umum presiden dan wakil presiden 2024 menjadi topik yang disoroti oleh khalayak, termasuk para pemilih muda atau bisa disebut Gen Z. Penggunaan media instagram oleh tiga kandidat calon presiden untuk melancarkan pengenalan diri dan kampanye pemilu menjadi rujukan pemilih gen Z dalam memberikan komentar dan penilaian. Riset ini bertujuan untuk mengetahui perilaku pemilih Gen Z pada Pilpres 2024, dengan menggunakan metode kualitatif netnografis dan analisis deskriptif. Hasil temuan kajian ini menunjukkan bahwa perilaku Gen Z dalam menyikapi Pilpres 2024 meliputi dua perilaku, yaitu perilaku rasional dan irasional. Perilaku rasional Gen Z ditampilkan dengan menilai visi dan misi pasangan calon presiden serta track record prestasinya., sedangkan perilaku irasional pemilih Gen Z ditunjukkan dengan memberikan penilaian kepada pasangan calon presiden berdasarkan konten yang menarik atau kepopuleran meskipun minim substansi. Oleh karena itu, temuan ini berkontribusi bagi pengembangan wacana berbasis pengguna yang dapat mendekonstruksi dominasi wacana oleh penguasa. Hal ini sejalan dengan nilai-nilai komunikasi Islam berupa ‘kebebasan berbuat’ yang menjamin setiap individu untuk menerima atau menolak suatu wacana.